2007
DOI: 10.1673/031.007.5001
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Five Chitin Synthesis Inhibitors Against the Colorado Potato Beetle,Leptinotarsa decemlineata

Abstract: Results of laboratory experiments are reported that tested the effects of five chitin synthesis inhibitors, diflubenzuron, cyromazine, lufenuron, hexaflumuron and triflumuron. on second instars of the Colorado potato beetle, Leptinotarsa decemlineata (Say) (Coleoptera: Crysomelidae), originally collected from potato fields of Bostanabaad, a town 66 km southeast of Tabriz, Iran. In bioassays, the larvae were fed potato leaves dipped in aqueous solutions containing chitin synthesis inhibitors. The mortalities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…These larvae were not able to feed, and eventually died. These results are consistent with results of Hughes et al (1986) and Karimzadeh et al (2007). Molting and metamorphosis are two critical physiological events in the life of insects.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These larvae were not able to feed, and eventually died. These results are consistent with results of Hughes et al (1986) and Karimzadeh et al (2007). Molting and metamorphosis are two critical physiological events in the life of insects.…”
Section: Resultssupporting
confidence: 93%
“…It may be concluded from these results that E. figulilella is more sensitive to hexaflumuron than lufenuron. Karimzadeh et al (2007) rated the toxicity of five different chitin synthesis inhibitors in the following order: hexaflumuron > lufenuron > diflubenzuron > triflumuron > cyromazine. Saenz-de-Cabezon et al (2006) found significant effects of lufenuron against different larval instars of L. botrana .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to potato, it devastates, by its voracious feeding, other solanaceous crops such as eggplant, tomato, pepper, and tobacco (Radcliffe 1982;Hare 1990;Metcalf & Metcalf 1993;Phyllis 2004). L. decemlineata can completely defoliate plants prior to tuber formation if not adequately controlled (Koopmanschap et al 1989;Zehnder & Evanylo 1989;Nault & Kennedy 1998;Karimzadeh et al 2007), and may reduce tuber yields by as much as 50% (Hare 1980). Moreover, this pest is widely considered as a quarantine pest in most countries of the world including Egypt (EPPO 2006).…”
mentioning
confidence: 99%
“…This plant is known to produce a range of terpinoids, flavonoids and pyrons. Karimzadeh et al (2007) Effects of five chitin synthesis inhibitors, diflubenzuron, cyromazine, lufenuron, hexaflumuron and triflumuron, on 2 nd instars of Leptinotarsa decemlineata. lufenuron and hexaflumuron seem to be more potent.…”
Section: Lufenuronmentioning
confidence: 99%